PENGGUNAAN KONTEN AI SURABAYA MILIK @BRANDONLILHERO DENGAN UNSUR BAHASA JAWA PADA TIKTOK SEBAGAI MEDIA PROMOSI - Maharani, Khalisa Khansa (The Commercium, 2023)
This study aims to find out how the use of @brandonlihero’s Ai Surabaya content containing Javanese language elements is used as promotional media. The researcher uses the 4C theory of social media by Chris Heuer. This research is a descriptive qualitative research using phenomenological methods. Collecting data in this study was obtained through interviews and observation. The results of this study indicate that the use of Ai Surabaya content has gone through several stages in accordance with Heuer’s 4C theory, namely context shown by humor content, relate content, packaging captions, themes, and language. Communication, namely through the delivery of product information and interaction with the audience. Collaboration through collaboration between Brandon and the brand. Connection, that is, apart from going through the comments column, Brandon maintains the relationship that has been built with the audience by being himself in the content.